The Effect of Job Rotation and Interpersonal Conflict on Work Productivity with Job Satisfaction as an Intervening Variable at the Transportation Service in NTB - Sauji, Pahrul; Asmony, Thatok; Nururly, Santi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of job rotation and interpersonal conflict on work productivity with job satisfaction as an intervening variable at the Transportation Agency in West Nusa Tenggara. This study is associative with a focus on causal relationships that influence each other. Data collection was carried out using a census method with questionnaire distribution techniques, interviews and documentation with all members of the population being used as respondents in this study. The population in this study were echelon 2, echelon 3, echelon 4 officials and all functional officials at the Transportation Agency in West Nusa Tenggara totaling 167 employees with a questionnaire response rate of 151 questionnaires or 90.42%. This study uses Structural Equation Modeling (SEM) using SmartPLS as an analysis. The results of the study indicate that job rotation has a significant positive effect on work productivity, while interpersonal conflict has a significant negative effect on work productivity. Job rotation has a positive and significant effect on job satisfaction and interpersonal conflict has a negative and significant effect on job satisfaction, in addition, job rotation has a positive and significant effect on work productivity through job satisfaction, and interpersonal conflict has a negative and significant effect on work productivity through job satisfaction. As shown by the Variance Axxounted For (VAF) value is 21% for job rotation and 36.5% for interpersonal conflict regarding work productivity